Analysis the Influence of GRDP, Population, and Provincial Minimum Wage on Open Unemployment in Bengkulu Province - Nur Asyifa Oktaliana; Mochamad Ridwan (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
Open unemployment in Bengkulu Province is allegedly likely to increase due to the economic recession and the Covid 19 pandemic, which is caused by fluctuations in GRDP, population and provincial minimum wages. This research aims to determine and analyze the influence of Gross Domestic Regional Product (GRDP), Population, and Provincial Minimum Wage on the Number of Open Unemployed in Bengkulu Province. The data used is secondary data sourced from BPS (Central Statistics Agency). The form of data used is panel data by taking the case of 1 city (Bengkulu City) and 3 parent districts (South Bengkulu, Rejang Lebong, North Bengkulu) in 2011-2020. The analysis method used is panel data regression with the Common Effect Model (CEM) approach. The research results show that simultaneously, the variables GRDP, Population and Provincial Minimum Wage influence Open Unemployment in Bengkulu province. Partially, the GRDP and Population variables have a significant and positive effect on Open Unemployment, while the Provincial Minimum Wage variable does not have a significant effect on Open Unemployment in Bengkulu province.